REVIEW OF SOME DIRECT AND INDIRECT METHODS USED TO MEASURE VO2 MAX IN PHYSICAL ACTIVITY AND SPORT (Fiep Bulletin - online, 2013)
A bibliographical revision was made, with the purpose of analyzing some of the direct and indirect methods that are used like tests or test, for the obtaining of the VO2 máx., being a this one fundamental variable in the scope of the clinical and sport medicine. Within the analysis of the direct methods, one is the Ergoespirometría, that it provides information to near the functional capacity of the individual and the VO2 máx., this test of effort is possible to be measured from the work made in a Cicloergómetro or Rolling Tape. In the conventional indirect methods, they appear the one of Course Navette, a maximum and progressive test that determines the aptitude cardiorespiratoria (Alvarez, J. ET to. 2001; Corral J. ET to. 2010), also, the test of Cooper is described who measures Maxima the aeróbica capacity of average duration in 12 minutes commonly used in the physical education.  In the analyzed nonconventional methods they appear: the TIVREBasket, determination of VO2 máx., from the corporal fat, proves stepped and determination of VO2 in children.  It is important to know, to apply and to develop to new methods for the obtaining of the VO2 máx., in the area of the sport, the physical activity and the physical education, for the validated determination of the yield and aeróbica power in different populations, considering different variable. Some methods like the one of Course Navette and test of Cooper, provide reliable information, are accepted by the scientific community and widely are used, other methods in process of specific validation have the advantage of being considering variable like the age, the IMC, the lipídico index, type of physical activity, deports and the ethnic differences marked by genetic differences.
Keywords: Methods; Physical activity.